ISDN - telekomunikacijska mreža budućnosti - Mikula, Miroslav (Promet - Traffic&Transportation, 2012)
The paper first deals with a review of technical properties and utilization potentials of the integrated digital network with common telecommunications services - the ISDN. The author then discusses the development of the ISDN in Europe and in Croatia. Finally the paper offers an assessment of the future development of the ISDN.